2013
DOI: 10.1159/000353862
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Index as a Diagnostic Tool for Patent Ductus Arteriosus in Preterm Infants

Abstract: Background: Perfusion index (PI) could reflect peripheral flow. Preterm infants with hemodynamically significant patent ductus arteriosus (hsPDA) will have left-to-right shunt across PDA causing less blood flow to the lower legs. Objective: To evaluate pre- and postductal PI differences (ΔPI) in hsPDA. Methods: Preterm infants with gestational age <34 weeks were assessed for ΔPI on days 1, 3, and 7 of life with simultaneous echocardiography. Based on echocardiography, each infant was categorized into hsPDA, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 15 publications
(22 reference statements)
3
18
1
Order By: Relevance
“…In the current study, there was a positive association with PI during the first 24 h and from 37 h onwards (when taking into account the hsPDA × time interaction) as also found by others [20]. One might expect a decrease in (peripheral) perfusion due to the ductal steal phenomenon and thereby a decrease in PI.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the current study, there was a positive association with PI during the first 24 h and from 37 h onwards (when taking into account the hsPDA × time interaction) as also found by others [20]. One might expect a decrease in (peripheral) perfusion due to the ductal steal phenomenon and thereby a decrease in PI.…”
Section: Discussionsupporting
confidence: 89%
“…Earlier studies have shown conflicting results concerning the effect of hsPDA on PI [20,21]. In the current study, there was a positive association with PI during the first 24 h and from 37 h onwards (when taking into account the hsPDA × time interaction) as also found by others [20].…”
Section: Discussionsupporting
confidence: 80%
“…These investigators concluded that in the presence of clinical signs of PDA and a delta PI of >1.05 %, the diagnosis of hsPDA should be considered. This test may be of special value in resource poor countries where echocardiography is not readily available [24]. Further studies are needed to confirm this finding.…”
Section: Delta Perfusion Index (Delta Pi)mentioning
confidence: 89%
“…Various approaches include interpretation of pulse oximetry information (perfusion index, plethysmography), (19)(20)(21) interpretation of transthoracic electrical signals (impedance, cardiometry, velocimetry, bioreactance), (22)(23)(24)(25) regional oxygenation (near-infrared spectroscopy), (26) alterations in skin microcirculation (side stream dark-field imaging, reflectance spectrophotometry), (27)(28) resonance Raman spectroscopy (Lauren J. Ruoss, personal communication, May 2018), and others.…”
Section: Diagnosismentioning
confidence: 99%